Global Overview of Anti-Bribery Laws 2016 - Baker&Mckenzie (Colección de libros electrónicos de ULoyola, 2016)
Baker & McKenzie has been global since inception. Being global is part of our DNA. Our difference is the way we think, work and behave ? we combine an instinctively global perspective with a genuinely multicultural approach, enabled by collaborative relationships and yielding practical, innovative advice. Serving our clients with more than 4,200 lawyers in more than 45 countries, we have a deep understanding of the culture of business the world over and are able to bring the talent and experience needed to navigate complexity across practices and borders with ease.